Single-crystalline boron-doped diamond superconducting quantum interference devices with regrowth-induced step edge structure - Taisuke Kageura (Nature Portfolio, 2019)
Abstract Superconducting quantum interference devices (SQUIDs) are currently used as magnetic flux detectors with ultra-high sensitivity for various applications such as medical diagnostics and magnetic material microstructure analysis. Single-crystalline superconducting boron-doped diamond is an excellent candidate for fabricating high-performance SQUIDs because of its robustness and high transition temperature, critical current density, and critical field. Here, we propose a fabrication process for a single-crystalline boron-doped diamond Josephson junction with regrowth-induced step edge structure and demonstrate the first operation of a single-crystalline boron-doped diamond SQUID above 2 K. We demonstrate that the step angle is a significant parameter for forming the Josephson junction and that the step angle can be controlled by adjusting the microwave plasma-enhanced chemical vapour deposition conditions of the regrowth layer. The fabricated junction exhibits superconductor–weak superconductor–superconductor-type behaviour without hysteresis and a high critical current density of 5800 A/cm2.